Sejarah perkembangan pendidikan Islam pada kerajaan-kerajaan Islam klasik di Jawa abad XV-XIX: Kajian historis dan komparatif - Sabrina Sahra; Putri Annisa; Idrus L Latif (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study discusses the development of Islamic education in the Javanese kingdoms from the 15th to the 19th century, with a historical and comparative approach. Its purpose is to map institutions, curricula, pathways, and key actors, compare patterns among kingdoms, and identify factors of transformation between religion, politics, and culture. The methods include literature review, archaeological sources, documentary sources, and descriptive analysis. The results show a diversity of educational models, influenced by power, networks of scholars, and state policies. Pesantren, royal madrasas, and scholars' schools complement each other, with different curricula and legitimacy. The main factors include the role of scholars, integration of economic policies, as well as trade and demographic dynamics. This study emphasizes the transfer of knowledge and regional Islamic identity that continues to develop contextually and adaptively.